Reflective practice in language teaching - Farrell, Thomas S. C. ca. 20./21. Jh (Cambridge elements, 2022)
This Element examines the concept of reflective practice in language teaching. It includes a brief description of what reflective practice is and how it is operationalized by two of its main protagonists, John Dewey and Donald Schön, as well as some of the limitations of their conceptions. This is used as an introduction to how the author further developed their conceptions when operationalizing reflective practice for language teachers through a five-stage framework for reflecting on practice for language teachers. The author then presents an in-depth case study of the reflections of an English as a Foreign Language (EFL) teacher working in Costa Rica as he moved through the five stages of the framework for reflecting on practice. The author then goes on to outline and discuss how reflective practice may be moved forward and calls attention to the importance of emotions in the process of reflection for language teachers